Pengaruh Pemilihan Metode Akuntansi terhadap Tingkat Underpricing Saham Perdana - Syaiful Ali; Jogiyanto Hartono (The Indonesian Journal of Accounting Research, 2013)
This paper studies the different effects of accounting method choices used by companies before initial public offerings to the underpricing during 1994-1999.  From the perspective of litigation theory avoidance, Neill, et al. (1995) found that IPO companies using income increasing accounting methods (liberal) have greater underpricing rate compared to the companies using income decreasing accounting methods (conservative). The result indicated that underwriter and issuers attempted to reduce their risks exposure.We examined 129 IPO companies listed in Jakarta Stock Exchange during 1994-1999 and the result showed that there is significant effects of accounting method for fixed assets depreciation variable and ownerships signal over the underpricing. It is consistent with Neill, et. al (1995) research that indicated income increasing accounting method choices for fixed assets depreciation (liberal) positively related with underpricing. However, the research failed to prove the effect of accounting method for inventory valuation that probably due to the insignificant of financial effects of average inventory valuation accounting method.